Indo-Pak conflict controlled mass communication - "Rao, Bhaskara N." (New Delhi, 1971)
In this volume Dr. N. Bhaskara Rao presents the findings and insights of his own extensive research in government documents and daily newspapers. He focuses the eye of analysis on both government decision-making and on the press of India and Pakistan. He studies the period of rising tension preceding the India-Pakistan conflict of 1965, then the period of actual war, and finally the period of slowly declining tensions. He searches in depth for indications on either side that one side is willing to grant in sonic degree the legitimacy of the other side's claim, or policy statement. Then he describes government behaviour as related to the opposing country and vice versa: likewise he measures (from newspaper editorials) the degree each side manifests suspicion or trust in the other side. International behavior research in the social sciences which Dr. Rao cites suggests the element of "trust" or "confidence" and their polar opposites "suspicion" of "hatred." as powerful national attitudes in international relations. In studying the way the indicators change over time, particularly during time of crisis and war, the author charts day by day how two great nations came to use force for the settlement of an international dispute.
Keywords: International Relations